Hydrological Performance of Green Roof Systems: A Numerical Investigation - Kim, Sang Yeob; Na, Wooyoung; Jun, Changhyun; Seo, Hyungjoon; Kim, Yongmin (Frontiers in Environmental Science, 2021)
Green roof systems could help reduce peak discharge and retain rainwater in urban areas. The objective of this study was to investigate the hydrological behavior of a green roof system by using the SEEP/W model. The rainfall-runoff relationship within the green roof system was simulated and the results were compared with actual data from a test bed for green roof systems to verify the applicability of SEEP/W. Then, the verified SEEP/W model was used to simulate the green roof system by varying four factors (soil type, rainfall intensity, substrate depth, and green roof slope) to explore the hydrological performance through the peak discharge to rainfall intensity (PD/RI) ratio and the rain water retention rate. The results show that the model presents slightly faster and greater peak time and peak discharge values, respectively, as compared to the observational data. This is attributed to the vegetation conditions in the real green roof system. However, it is also shown that the SEEP/W model can be used to design green roof systems and evaluate their hydrological behavior because of its modeling efficiency. Thus, the SEEP/W model can be used to reliably design and manage green roof systems by further considering the vegetation conditions and water flow dynamics. Furthermore, it would be desirable to consider additional factors, such as vegetation and an insulating pebble layer, in the design and management of green roofs in future work.